The Most Types of Speaking Feedback on Students Between Covid-19 and Post Covid-19 Pandemic Era - Putra, Anggie Eka Permana; Irawan, Rifki (Universitas PGRI Yogyakarta, 2024)
ABSTRACT In the era of the covid-19 and post-covid-19 pandemics, there were many changes, especially in education. This made feedback have to be conveyed perfectly even in both online and offline learning. This study aimed to compare the types of feedback and to explore the types and how feedback was given by lecturers to students in understanding speaking between the covid-19 and post covid-19 pandemic. This research used a qualitative methodology with a case study as an approach. The finding data of this study was presented verbally rather than through computation or numerical data, in the form of words or descriptive data. This study used in-class observation and interviews with four respondents. With this approach, the research sought to understand in-depth and in detail about the phenomenon under study, explored understanding from the perspective of the respondents, and analyzed various information collected to formulate meaningful findings. The results of this study show that feedback plays a vital role in higher education, improving student learning and academic performance. Corrective feedback is the most common type mentioned. Students' application of feedback depends on their perspectives and the support available for implementation. The absence of feedback can negatively impact understanding and direction in learning. However, applying feedback leads to positive changes and improves performance. Post COVID-19 offline learning is preferred by students compared to the challenges of online learning during the pandemic. Keywords: COVID-19 Pandemic era, Feedback, Lecturers, Students